Pengembangan Multimedia Pembelajaran Berbasis Web Pada Mata Pelajaran IPA Kelas VIII SMP - Mahareni, Yolanda; Syafril, Syafril; Anugrah, Septriyan; Kurnia, Reni (Indo-MathEdu Intellectuals Journal, 2024)
The lack of utilization of learning media is one of the factors in students' low understanding of the material discussed and students feel bored during the learning process. Science subjects are one of the subjects that have a high level of understanding, one of the materials is animal cells and plant cells, therefore multimedia learning can help visualize this concept so that it is easier for students to understand. This research aims to find out how the process of developing multimedia learning and find out the results of validity tests and practicality tests. The development used is Research & Development (R&D). with a development model, namely a 4D model consisting of define, design, develop and disseminate. The results of the data analysis showed that the media validity with validator 1 got an average result of 4.93 in the "very valid" category and the result with validator 2 got an average of 4.80 in the "very valid" category. The acquisition of material validity by material validators obtained an average result of 4.80 with the category of "very valid". This learning multimedia is practical based on a practicality test with an average of 4.52. Based on the results of the practicality test, it was concluded that multimedia learning in science subjects in grade VIII junior high school can be used in the teaching and learning process.